Konsep al-Jizyah dan Status Kewarganegaraan Non-Muslim dalam Prespektif Fikih Klasik - Muflikhatul Khairah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2007)
In the concept of islamic jurisprudence, the authority of state is divided into three domains: domain of Islam(dar al-Islam), Domain of enemy (dar al-kufr), and domain of treaty(dar al-‘ahd). The inhabitants of dar al-Islam is catagorized into two; muslim inhabitants and non-muslim inhabitants. Those non-muslim living in dar al-Islam is called ahl al-dhimmah, that is a civil status with a consequence of paying yearly personal tax to Muslim authorityjizyah. The payment of jizyah is modern context is problematic for many reasons. For some Muslim jurists jizyah cannot be enacted any longer since it is contradictory to human rights. In addition, orientalists have negatively labeled Islam because jizyah is discriminatory. On that basis, the article discusses the issue with following postulates; whether jizyah truly contradictory to the values of human rights and therefore discriminatory. It is found out that such assumption is incorrect because of no historical background that can support the claim. On the contrary, jizyah , as shown in al-Qur’an and Hadith does not contain discrimination or even jeopardize the position of dhimmy. Instead, jizyah is an indication of the justice of Islamic law.